Huella hídrica y educación ambiental en gestión del recurso hídrico en Nina Rumi, San Juan Bautista, Loreto, 2023 - Navarro Tuesta, Nixon Ezequiel (2024)
The research carried out in the community of Nina Rumi, San Juan Bautista, 2023, in order to quantify the water footprint in homes and evaluate environmental education in water resource management, using the calculator established by the ANA and a survey designed for this purpose. The population was 950 inhabitants grouped in 350 households, in a sample of 60 heads of households. The 60% of the population consumes between 100 and 200 bottles of water daily, 38% consume between 4,688 and 6,770 liters of water monthly. Regarding water footprint and environmental education, 65% agree with reducing their consumption, however, 52% disagree and do not know about water footprint and its calculation, 57% do not participate in environmental education workshops. On water resource management, 50% report disagreement on strategies for water conservation, but 38% say they agree to promote education and awareness about the importance of water, 48% are in favor of adopting new technologies in water resource conservation.